Schwindel und Blutdruck - Middeke, Martin (DMW - Deutsche Medizinische Wochenschrift, 2019)
Dizziness is most frequently caused by blood pressure dysregulation comprising a broad spectrum from constitutional and orthostatic hypotension to severe conditions like endocrinopathies and neurodegenerative diseases with autonomic dysfunction like in multiple system atrophy.
Keywords: Schwindel; Hypotonie; ambulante Blutdruck-Langzeitmessung